Pengaruh Institusi Terhadap Derajat Desentralisasi Fiskal di Indonesia - Puspita Chaniago, Rezi; Usman, Moneyzar; Ananta, Prayudha (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
The main issue underlying this research is the significant disparity in the degree of fiscal decentralization among provinces in Indonesia, particularly between provinces in Java and outside Java, and the persistently high fiscal dependency of several regions on the central government. This study aims to analyze the influence of democracy, economic growth, Gini ratio, and population size on the degree of fiscal decentralization in Indonesia. Using panel data from 32 provinces during the 2012-2023 period, this research applies a Random Effect Model (REM) with robust standard error. The results show that democracy, economic growth, and population size have positive and significant effects on the degree of fiscal decentralization, while the Gini ratio shows no significant influence. These findings imply that improvements in democratic quality, economic growth, and optimization of demographic potential can strengthen regional fiscal independence. This research recommends that local governments focus their policies on strengthening democratization, increasing economic growth, and optimizing human resource potential to enhance regional fiscal independence.